2022
DOI: 10.1002/jmv.27974
|View full text |Cite
|
Sign up to set email alerts
|

Viral load of SARS‐CoV‐2 Omicron is not high despite its high infectivity

Abstract: Patients infected with the Omicron variant of severe acute respiratory syndrome coronavirus 2 has increased worldwide since the beginning of 2022 and the variant has spread more rapidly than the Delta variant, which spread in the summer of 2021. It is important to clarify the cause of the strong transmissibility of the Omicron variant to control its spread. In 694 patients with coronavirus disease 2019, the copy numbers of virus in nasopharyngeal swab‐soaked samples and the viral genotypes were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
7
19
0
Order By: Relevance
“…As reported previously by the authors 3 , the median copy number of Delta variant samples from July 2021 to January 2022 was 1.5 × 10 5 copies/μL ( n = 290). The median copy number of BA.5 in this study was significantly lower than that of Delta cases in a previous study ( p < 0.0001).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As reported previously by the authors 3 , the median copy number of Delta variant samples from July 2021 to January 2022 was 1.5 × 10 5 copies/μL ( n = 290). The median copy number of BA.5 in this study was significantly lower than that of Delta cases in a previous study ( p < 0.0001).…”
Section: Discussionsupporting
confidence: 82%
“…This enabled the testing of the exact copy number and variant types of SARS-CoV-2 in nasopharyngeal swab samples from these patients who visited the hospital. The authors’ previous study has reported that there was no significant difference in the copy numbers between the Delta variant cases and Omicron variant cases, the latter of which mainly involved BA.1, as well as BA.2 to a certain extent 3 .…”
Section: Introductionmentioning
confidence: 91%
“…Firstly, it is not certain that future viral evolution will necessarily lead to a decrease in clinical severity. The Omicron variant does not cause higher viral loads in the respiratory tract than the Delta variant (with some research suggesting that these loads may even be lower) [ 38 , 39 , 40 ]; moreover, it has no greater affinity to the angiotensin-converting enzyme-2 receptor, and is less fusogenic [ 41 , 42 ]. Considering that SARS-CoV-2 is most transmissible prior to symptoms onset and at the beginning of the symptomatic phase [ 43 ], the mutation-enhancing viral loads could lead to superior transmission, yet be accompanied by more severe infections due to increased risk of hyperinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that viral loads in upper respiratory tract were lower in patients with Omicron variant infection than in those with prior variant infection. 8 , 9 , 10 In addition, Omicron variant infection had similar incubation period compared with Delta variant infection. 11 These data suggest that high transmissibility may not be due to the viral load itself or the incubation period, but due to more efficient viral replication in upper respiratory tract.…”
Section: Introductionmentioning
confidence: 86%